Genome-wide association study of nausea and vomiting during pregnancy in Japan: the TMM BirThree Cohort Study - Yudai Yonezawa; Ippei Takahashi; Hisashi Ohseto; Fumihiko Ueno; Tomomi Onuma; Aoi Noda; Keiko Murakami; Mami Ishikuro; Taku Obara; Shinichi Kuriyama (BMC Pregnancy and Childbirth, 2024)
Abstract Background Nausea and vomiting during pregnancy (NVP) and hyperemesis gravidarum (HG), common conditions affecting most pregnant women, are highly heritable and associated with maternal and fetal morbidity. However, the pathologies underlying NVP and HG and their associated loci are scarce. Methods We performed genome-wide association studies (GWAS) of NVP in pregnant women (n = 23,040) who participated in the Tohoku Medical Megabank Project Birth and Three-Generation Cohort Study in Japan from July 2013 to March 2017. Participants were divided into discovery (n = 9,464) and replication (n = 10,051) stages based on the platform used for their genotyping. Loci that achieved the genome-wide significance level (p < 5.0 × 10− 8) in the discovery stage were selected for genotyping in the replication stage. A meta-analysis integrating the discovery and replication stage results (n = 19,515) was conducted. NVP-related variables were identified as categorical or continuous. Results GWAS analysis in the discovery phase revealed loci linked to NVP in two gene regions, 11q22.1 (rs77775955) and 19p13.11 (rs749451 and rs28568614). Loci in these two gene regions have also been shown to be associated with HG in a White European population, indicating the generalizability of the GWAS analyses conducted in this study. Of these, only rs749451 and rs28568614 at 19p13.11 reached the genome-wide suggestive level (p < 1.0 × 10− 5) in the replication stage; however, both loci were significant in the meta-analysis. Conclusions NVP-related loci were identified in the Japanese population at 11q22.1 and 19p13.11, as reported in previous GWAS. This study contributes new evidence on the generalizability of previous GWAS on the association between genetic background and NVP.